2012
DOI: 10.1007/978-3-642-33687-4_3
|View full text |Cite
|
Sign up to set email alerts
|

A Serious Game for Training Balance Control over Different Types of Soil

Abstract: It is known that the type of the soil can affect balance. Here we report a serious game designed for training users at maintaining balance over five types of soil (broken stone, stone dust, sand, concrete and wood). By using an augmented shoe and proposed navigation metaphor, in this game, the user is invited to browse a maze with standing balance over the physical grounds. During the exploration, exercises targeting assessment balance control are suggested. To insure the effectiveness of this training program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Recently, a Smartphone software has proved to be an effective tool for showing clinical tests parameters at home [25]. Other studies showed that a Smartphone-based system may be used for assessing risk of falling [12] and for training users at maintaining balance [26] over different types of ground [27] by using a serious game. These recent studies have shown that mobile systems can be used for assessing clinical test parameters.…”
Section: A Technologies For Gait and Balance Disorder Analysismentioning
confidence: 99%
“…Recently, a Smartphone software has proved to be an effective tool for showing clinical tests parameters at home [25]. Other studies showed that a Smartphone-based system may be used for assessing risk of falling [12] and for training users at maintaining balance [26] over different types of ground [27] by using a serious game. These recent studies have shown that mobile systems can be used for assessing clinical test parameters.…”
Section: A Technologies For Gait and Balance Disorder Analysismentioning
confidence: 99%
“…Recently, a Smartphone application has proved to be an effective tool for showing clinical tests parameters at home [14]. Other studies showed that a Smartphone-based system may be used for assessing risk of falling [15] and for training users at maintaining balance [16] over different types of ground [17] by using a serious game. These recent studies have shown that mobile systems can be used for assessing clinical test parameters.…”
Section: A Technologies For Gait and Balance Disorder Analysismentioning
confidence: 99%
“…Among them, recent papers focus on automatics balance tests. In [12], sensors incorporated in the sole of a shoe are used to assess balance on different type of soil of a maze. In the same way, in [13] a serious game for evaluating balance capability using the Berg Balance Scale is designed and evaluated.…”
Section: Related Workmentioning
confidence: 99%